Systematic evaluation of therapeutic effectiveness of Azvudine in treating COVID-19 hospitalized patients: a retrospective cohort study - Xu, Yingkai; Huang, Yuan; Yuan, Zihan; Liu, Wanbing (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAzvudine, a repurposed oral small molecule antiviral drug, has potential effects in combating the SARS-CoV-2 virus. However, studies on its clinical efficacy in patients with COVID-19 are still limited and controversial, and further research and validation are necessary.MethodsA retrospective cohort study was conducted on COVID-19 patients who were hospitalized in the General Hospital of Central Theater Command from 1 December 2022 to 31 January 2023. We included 132 patients treated with Azvudine and 132 controls after screening and propensity score matching. The primary outcomes including all-cause mortality and a composite outcome of disease progression such as non-invasive respiratory support, invasive respiratory support, admission to intensive care unit (ICU), and death were compared.ResultsAzvudine recipients had a much lower incidence rate of composite disease progression outcome than controls (13.9075/1000 person-days versus 25.7731/1000 person-days, P<0.05). Azvudine recipients also possessed a lower all-cause mortality rate than controls (2.6797/1000 person-days versus 8.5910/1000 person-days, P<0.01). Azvudine treatment significantly reduced the risk of composite disease progression (HR: 0.37, 95% CI: 0.16-0.84, P=0.017) and all-cause death (HR: 0.25, 95% CI: 0.08-0.81, P=0.021) after adjusting potential confounding factors such as age, sex, severity of COVID-19, complications, concomitant therapy, time from symptoms to treatment, and important laboratory indicators. The subgroup analyses of composite disease progression outcome and all-cause death indicated robustness of Azvudine’s in treating COVID-19 patients in general.ConclusionOur study demonstrates that Azvudine has a significant positive impact on the clinical recovery of hospitalized patients with COVID-19. These findings provide important support for the use of Azvudine as a therapeutic option for COVID-19, given the current divergent views on its therapeutic efficacy and its importance in public health and medical care.